2013
DOI: 10.1242/jcs.126599
|View full text |Cite|
|
Sign up to set email alerts
|

The phosphorylation of ARPP19 by Greatwall renders the autoamplification of MPF independent of PKA in Xenopus oocytes

Abstract: Entry into mitosis or meiosis relies on the coordinated action of kinases and phosphatases that ultimately leads to the activation of Cyclin B-Cdk1, also called MPF for M-phase promoting factor. Vertebrate oocytes are blocked in prophase of the first meiotic division, an arrest tightly controlled by a high PKA activity. Reentry into meiosis depends on Cdk1 activation that obeys a two steps mechanism: a catalytic amount of Cdk1 is generated in a PKA and protein synthesis-dependent manner; then a regulatory netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
107
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(117 citation statements)
references
References 62 publications
9
107
1
Order By: Relevance
“…We also generated a nonphosphorylatable ARPP19 mutant at S67 by mutating S67 into an alanine (S67A-ARPP19). The S67A-ARPP19 mutant proved to be a strong inhibitor of meiosis resumption in response to either progesterone or PKI injection but also following the overexpression of constitutive active Gwl [110]. These results clearly demonstrate that ARPP19, once phosphorylated by Gwl at S67, is involved in the Cdk1 autoamplification loop by directly inhibiting PP2A-B55δ (Figure 7).…”
Section: The Phosphorylation Of Arpp19 At S67 By Gwl Promotes Cdk1 Acmentioning
confidence: 74%
See 3 more Smart Citations
“…We also generated a nonphosphorylatable ARPP19 mutant at S67 by mutating S67 into an alanine (S67A-ARPP19). The S67A-ARPP19 mutant proved to be a strong inhibitor of meiosis resumption in response to either progesterone or PKI injection but also following the overexpression of constitutive active Gwl [110]. These results clearly demonstrate that ARPP19, once phosphorylated by Gwl at S67, is involved in the Cdk1 autoamplification loop by directly inhibiting PP2A-B55δ (Figure 7).…”
Section: The Phosphorylation Of Arpp19 At S67 By Gwl Promotes Cdk1 Acmentioning
confidence: 74%
“…Cdc25 to launch the loop [70,103,105,109,110]. In contrast, PKA activity does not prevent the autoamplification loop when triggered by the inhibition of PPPs [17,104].…”
Section: Protein Phosphorylationmentioning
confidence: 97%
See 2 more Smart Citations
“…Using frog oocytes, Olivier Haccard (CNRS, UPMC UMR7622, Paris, France) demonstrated that the phosphorylation of ARPP19 by Greatwall, which is controlled by basal levels of Cdk1, promotes the binding of ARPP19 to PP2A-B55, thereby inhibiting PP2A. This phosphorylation event renders the MPF auto-amplification independent of PKA (Dupré et al, 2013). The involvement of Greatwall and ARPP19 in MPF activation is conserved between starfish and frog, and it will be interesting to assess whether they also participates in MPF autoamplification in other species, such as invertebrates (Cnidarian or C. elegans) or simple marine chordates (urochordates).…”
Section: Cell Cycle Regulationmentioning
confidence: 99%